Affect and Gender in Cormac McCarthy’s Outer Dark - Julia Tulloh Harper (European Journal of American Studies)
Cormac McCarthy’s 1968 novel, Outer Dark, is arguably his only text that contains a true female protagonist. Rinthy Holme is a significant character in her own right, in part because almost half the storyline is dedicated to her, but also because she seems to generate what scholars have referred to as a sense of forcefulness or meaningfulness that is sometimes at odds with otherwise more problematic elements of her characterization. By focusing on a small excerpt of Outer Dark, I argue that Rinthy feels meaningful because of the affective resonances that the text that describes her seems to emanate, rather than solely as a result of any diegetic aspect of her characterization. I draw on Brian Massumi’s account of affect to illuminate the apparent disconnect between the content of the text about Rinthy and its actual physical effects on readers, as well as the textual operations that might cause these effects. I also investigate, however, whether Rinthy’s affective power is truly able to combat other more problematic elements of her characterization, such as her apparently essentialized maternal instinct and empathy. I conclude by arguing that although the excerpt analyzed demonstrates a powerful instance of McCarthy’s interest in the centrality of the material in the process of meaning-making, and also perhaps suggests that McCarthy gestures towards the ways in which women might engage in the world as independent, embodied agents, McCarthy ultimately cannot escape an essentialized male/female binary.